2009
DOI: 10.1143/apex.2.046501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressurization on the Dynamics of a Cavitation Bubble Induced by Liquid-Phase Laser Ablation

Abstract: We applied external high pressure to ambient water in liquid-phase laser ablation. As a result, it was found that the maximum volume V max of a cavitation bubble induced by laser ablation satisfied a scaling law of V max / P À1 ext with P ext being the pressure applied to water. The effect of the pressurization was also observed in the shape of the second bubble induced by the collapse of the first cavitation bubble. These experimental results indicate that the dynamics of a cavitation bubble induced by liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 16 publications
7
107
1
Order By: Relevance
“…The results from this experiment were similar to those shown by Sasaki et al [9] , who induced a cavitation bubble in a fluid at different pressures, but using a higher pressure than in the present experiments. In both studies from Sasaki et al [9] and our research group, the external pressure applied on the liquid affects the bubbles collapse time, consequently according to the Rayleigh-Plesset relation, the maximum bubble radii were also affected.…”
Section: Collapse Time and External Liquid Pressuresupporting
confidence: 92%
See 1 more Smart Citation
“…The results from this experiment were similar to those shown by Sasaki et al [9] , who induced a cavitation bubble in a fluid at different pressures, but using a higher pressure than in the present experiments. In both studies from Sasaki et al [9] and our research group, the external pressure applied on the liquid affects the bubbles collapse time, consequently according to the Rayleigh-Plesset relation, the maximum bubble radii were also affected.…”
Section: Collapse Time and External Liquid Pressuresupporting
confidence: 92%
“…This bouncing behavior remains for several subsequent bubbles [4,8] . Some authors also have studied the phenomenon of induced cavitation in pressurized fluid [9] using shadowgraphy.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing repetition rate signifies a reduction of the temporal interpulse distance, which could cause an overlap of subsequent pulses and cavitation bubble lifetimes. Sasaki et al reported the lifetime of the cavitation bubble for nanosecond laser pulses at ambient pressure to be 15-200 μs [43], and for picosecond laser pulses Wagener et al determined a threshold of 5 kHz (equivalent to 200 μs interpulse distance) [40]. A further increase of the repetition rate creates a shielding effect by the cavitation bubble of the previous pulse which affects ablation efficiency.…”
Section: Laser-based Synthesismentioning
confidence: 99%
“…The cavitation bubble is a remarkable phenomenon of liquid-phase laser ablation, and is induced as a result of the abrupt formation of a laser-produced plasma in the liquid [33][34][35]. The cavitation bubble has the dynamics of expansion, shrinkage, and collapse.…”
Section: Introductionmentioning
confidence: 99%